PERSONAL ORIENTED LEADERSHIP IN EDUCATIONAL INSTITUTION MANAGEMENT (Educological discourse, 2016)
The article discusses the evolution of approaches to defining the essence of leadership: leadership as a position in the organization, role; leadership as a set of individual traits; leadership as a set of individual skills; leadership as behaviour, style. The attention is focused on the fact that replaced the authoritarian style of governance and the leader’s main role in organisation, including in education, comes orientation on democratic norms, values and active participation of employees in the management of educational institutions. Theories of leadership with their singular focus on the personality, the individual leader’s traits and skills do not reflect the whole diversity of processes that arise at educational institutions.